Methionine on the rise: how mitochondria changed their codon usage. (30th August 2016) - Boos, Felix; Wollin, Michael; Herrmann, Johannes M
Abstract : The tRNA specific for methionine (tRNA M et ) of human mitochondria contains a formyl‐cytosine at the wobble position of the anticodon to facilitate its binding to AUG, AUA and (in one instance) to AUU. In this issue of The EMBO Journal, Haag et al identify a two‐step enzyme pathway facilitating the modification of the tRNA. Sequential reactions of the methyltransferase NSUN3 and the dioxygenase ALKBH1/ABH1 are important to render the tRNA as able to recognize the non‐canonical methionine codons AUA and AUUs, a property critical for efficient protein synthesis in human mitochondria. Abstract : The discovery that NSUN3 and ABH1 specifically modify mt‐tRNA Met sheds light on the basis for efficient translation in mitochondria.